NOD2 Influences Trajectories of Intestinal Microbiota Recovery After Antibiotic PerturbationSummary - Jacqueline Moltzau Anderson; Simone Lipinski; Felix Sommer; Wei-Hung Pan; Olivier Boulard; Ateequr Rehman; Maren Falk-Paulsen; Stephanie T. Stengel; Konrad Aden; Robert Häsler; Richa Bharti; Sven Künzel; et al. (Cellular and Molecular Gastroenterology and Hepatology, 2020)
Background & Aims: Loss-of-function variants in nucleotide-binding oligomerization domain-containing protein 2 (NOD2) impair the recognition of the bacterial cell wall component muramyl-dipeptide and are associated with an increased risk for developing Crohn’s disease. Likewise, exposure to antibiotics increases the individual risk for developing inflammatory bowel disease. Here, we studied the long-term impact of NOD2 on the ability of the gut bacterial and fungal microbiota to recover after antibiotic treatment. Methods: Two cohorts of 20-week-old and 52-week-old wild-type (WT) C57BL/6J and NOD2 knockout (Nod2-KO) mice were treated with broad-spectrum antibiotics and fecal samples were collected to investigate temporal dynamics of the intestinal microbiota (bacteria and fungi) using 16S ribosomal RNA and internal transcribed spacer 1 sequencing. In addition, 2 sets of germ-free WT mice were colonized with either WT or Nod2-KO after antibiotic donor microbiota and the severity of intestinal inflammation was monitored in the colonized mice. Results: Antibiotic exposure caused long-term shifts in the bacterial and fungal community composition. Genetic ablation of NOD2 was associated with delayed body weight gain after antibiotic treatment and an impaired recovery of the bacterial gut microbiota. Transfer of the postantibiotic fecal microbiota of Nod2-KO mice induced an intestinal inflammatory response in the colons of germ-free recipient mice compared with respective microbiota from WT controls based on histopathology and gene expression analyses. Conclusions: Our data show that the bacterial sensor NOD2 contributes to intestinal microbial community composition after antibiotic treatment and may add to the explanation of how defects in the NOD2 signaling pathway are involved in the etiology of Crohn’s disease.